Optimization of Energy and Nitrogen Availability for Microbial Protein Synthesis and Growth Performance of Crossbred Calves - Ayyappan, K.; Singh, B.; Singhal, K.K. (Indian Journal of Animal Nutrition, 2018)
A study was conducted to assess the effect of dietary synchrony of energy and nitrogen (N) release in rumen on microbial protein synthesis and growth performance in crossbred calves. Two isonitrogenous and isocaloric diets were formulated on the basis of hourly OM and N degradation of each ingredient and the synchrony index (SI) of synchronous (S, SI 0.82) and asynchronous (AS, SI 0.57) diets were evaluated for microbial protein synthesis in vitro. The values of total gas and methane production were higher (P